Evaluation of the Endo-Uro trainer for semi-rigid ureteroscopy training. (September 2019) - Palaneer, Sharanya; Aydin, Abdullatif; Janabi, Hasaneen Al; Al-Jabir, Ahmed; Macchione, Nicola; Khan, Muhammad Shamim; Dasgupta, Prokar; Ahmed, Kamran
Background: The aim of this study was to evaluate the validity of evidence of the Endo-Uro Trainer (SAMED, Dresden, Germany) for semi-rigid ureteroscopy. Methods: Novice ( n = 29), intermediate-level ( n = 25), and expert ( n = 24) urological surgeons were recruited to participate in the study. Novices were allocated randomly to Groups A and B, where A performed two set procedures using the already validated Uro-Scopic Trainer (Limbs and Things, Bristol, UK), and Group B used the Endo-Uro trainer. Subsequently they were crossed over to perform the same two procedures using the other model. Intermediate and expert groups performed the same procedure on the Endo-Uro trainer only. Objective Structured Assessment of Technical Skills (OSATS) and the procedural times were collected and analyzed. All participants were invited to complete a final evaluation survey. Results: The evaluation survey revealed a realism rating in all aspects, with a mean Likert rating of 4.04/5. Significant differences were observed in performance time between novices and experts ( p = 0.0014), and between intermediates and experts ( p = 0.0113). OSATS scores differed significantly between all groups ( p < 0.0001). Group B novices showed statistically significant improvement in performance time ( p = 0.0012) and OSATS scores ( p = 0.0439) after the crossover. Significant differences in performance time ( p = 0.0025) between groups A and B were also observed post-crossover. Conclusions: This study demonstrated content validity for the Endo-Uro Trainer model. In addition, the model was shown to be capable of differentiating levels of experience, which contributes to the acceptance of the validity hypothesis. Improvement in performance using the model demonstrates its effectiveness for training.